Plk1 regulates contraction of postmitotic smooth muscle cells and is required for vascular homeostasis - de Cárcer, Guillermo; Wachowicz, Paulina; Martínez Martínez, Sara; Oller, Jorge; Méndez Barbero, Nerea; Escobar, Beatriz; González Loyola, Alejandra; Takaki, Tohru; El Bakkali, Aicha; Cámara, Juan A; Jiménez Borreguero, Luis Jesús; Bustelo, Xosé R; et al. (My University, 2017)
Polo-like kinase 1 (PLK1), an essential regulator of cell division, is currently undergoing clinical evaluation as a target for cancer therapy. We report an unexpected function of Plk1 in sustaining cardiovascular homeostasis. Plk1 haploinsufficiency in mice did not induce obvious cell proliferation defects but did result in arterial structural alterations, which frequently led to aortic rupture and death. Specific ablation of Plk1 in vascular smooth muscle cells (VSMCs) led to reduced arterial elasticity, hypotension, and an impaired arterial response to angiotensin II in vivo. Mechanistically, we found that Plk1 regulated angiotensin II¿dependent activation of RhoA and actomyosin dynamics in VSMCs in a mitosis-independent manner. This regulation depended on Plk1 kinase activity, and the administration of small-molecule Plk1 inhibitors to angiotensin II¿treated mice led to reduced arterial fitness and an elevated risk of aneurysm and aortic rupture. We thus conclude that a partial reduction of Plk1 activity that does not block cell division can nevertheless impair aortic homeostasis. Our findings have potentially important implications for current approaches aimed at PLK1 inhibition for cancer therapy.